PENGARUH PENGAWASAN, LINGKUNGAN KERJA, FASILITAS KERJA TERHADAP PRESTASI KERJA PEGAWAI DINAS PANGAN DAN PERTANIAN KOTA TANJUNGBALAI - Azhari .; Widyaseno Trusyuwono; Rahwati .; Ahmad Zen; Siti Aminah Nasution (Manajemen dan Bisnis, 2021)
The  formulation  of  the  problem  in  this  research  is:  How  do  the  effects  of supervision, work environment, work facilities on the work performance at Dinas Pangan Dan Pertanian Kota Tanjungbalai. This study aims to determine the effect of supervision, work environment, work facilities on employee performance. With a non probability sampling technique, the sample in this study was 38 people. The results showed; Partial supervision has a positive effect on employee work performance  of 3,937; The work environment  partially has a positive effect on employee work performance  by 2,942; Work facilities partially have a positive effect on employee work performance of 3.507; Supervision, work environment and  work  facilities  simultaneously  have  a  positive  and  significant  effect  on employee work performance of 31.188.